Serbia in the Eve of the Revolution 4.0 - Bazić, Jovan R. (Sociološki pregled, 2019)
A review of this book is presented through a dialectical-synthetic approach which discusses various issues of the state of Serbian science and development of Serbia at a time of great technological innovation in the world. It is about integrated development, which includes science, education and culture, as generators of social development, because only they are able to respond to the complex temptations of the modern world and offer a vision of development.